Reverse Effect of Opuntia ficus‐indica L. Juice and Seeds Aqueous Extract on Gastric Emptying and Small‐Bowel Motility in Rat. Issue 1 (22nd November 2017) - Rtibi, Kaïs; Selmi, Slimen; Saidani, Khouloud; Grami, Dhekra; Amri, Mohamed; Sebai, Hichem; Marzouki, Lamjed
Abstract: This study was conducted to compare the effects of juice and seeds on gastric emptying, small‐bowel motility and intestinal ion transport. Separate groups of rats were randomized to receive NaCl, increasing doses of juice (5, 10, and 20 mL/kg, b.w.) or seeds aqueous extract (100, 200, and 400 mg/kg, b.w.). Simultaneously, two other groups were received, the reference drugs; clonidine (1 mg/kg) and yohimbine (2 mg/kg). The charcoal meal was used as a suspension for gastrointestinal motility test. The purgative action of juice was confirmed using the loperamide (5 mg/kg, p.o.) induced constipation. To evaluate the antisecretory effect, we were used as a hypersecretion agent, the castor oil at the dose of 5 mL/kg. Compared to the control and standard groups, we were showed that the prickly pear has an opposite effect on small‐bowel motility and gastric emptying. Indeed, the juice at various doses has a laxative effect of gastrointestinal transit in healthy and constipated‐rats. However, the aqueous extract of the seeds leads to a reduction of motility in normal rats which gives it a remarkable antidiarrhoeal activity, a notable intestinal fluid accumulation decline and electrolyte concentrations reestablishment. Moreover, orally juice administered at different doses accelerated the stomach emptying time in contrast to the seeds aqueous extract. More importantly, a significant variation in the phytochemical constituents levels between juice and seeds was found. These findings confirm the reverse therapeutic effects of this fruit in the treatment of digestive disturbances such as difficulty stool evacuation and massive intestinal secretion, likewise, the gastric emptying process perturbation.